Terrifier [videorecording (DVD)] - Leone, Damien; Leone, Damien; Leone, Damien; Kanell, Jenna; Scaffidi, Samantha; Thornton, David Howard (Dread Central, 2020)
Two women leave a Halloween party and head to a pizza joint unaware that a serial killer follows them.